Palmoplantar lesions of lichen planus - Surabhi Sinha; Rashmi Sarkar; Vijay Kumar Garg (Wolters Kluwer Medknow Publications, 2018)
Introduction: Palmoplantar lesions of lichen planus (LP) are uncommon and may not always have classical clinical features of LP. A variety of morphological types has been described in literature. Aim and Objectives: The aim was to study and classify the clinical variants into distinct easily recognisable categories for quick recognition and early treatment initiation. Methods: All patients diagnosed with LP over a period of 5 years were evaluated for palmoplantar lesions in our hospital. The clinical and histopathological features of the palmoplantar lesions were then studied. Results: Out of 424 patients of LP, 55 (12.9%) had palmoplantar lesions. Histopathology was consistent or at least compatible with LP in 44/55 patients. For the purpose of assessment, only patients with histopathology consistent with LP were included (n = 44) in the study. Just over half of the patients were male, with most patients (43.2%) having had LP lesions elsewhere for 6 months before palmoplantar lesions were noticed. Soles were more frequently involved than palms. The sites most often involved were the centre of the palms (45.2%), and the instep of the soles (63.9%). The predominant morphological presentation was psoriasiform (47.7%). One patient had ulcerative lesions of LP on both his soles which is a very rare variant. Notably, nearly half of the patients (20/44) had mucosal (mostly oral) lesions characteristic of LP. This was significant as typical oral lesions of LP help in identifying palmoplantar lesions that do not have classical lichenoid morphology. Conclusion: LP lesions on palms and soles need to be identified keeping a high index of suspicion and differentiated from other papulosquamous conditions so that specific treatment can be initiated early.